(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the methodology of utilizing interactive teaching methods in primary grade education. It discusses the benefits of these methods in enhancing student engagement, promoting collaborative learning, and improving academic outcomes. By integrating various interactive techniques such as group activities, hands-on projects, and technology-based tools, educators can create a dynamic and inclusive learning environment that caters to diverse learning styles